The Influence of Awareness and Service Quality on Taxpayer Compliance in Paying Land and Building Tax (PBB) in East Cikarang District in 2024 - Mita Sari; Daryanto , Daryanto (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the influence of Land and Building Tax (PBB) on taxpayer awareness and the quality of tax services on taxpayer compliance. This study uses a quantitative approach with an associative method and multiple linear regression analysis techniques. The data used are primary data obtained from questionnaires distributed in East Cikarang District. The results are expected to demonstrate a significant influence, both partially and simultaneously. These findings will serve as a basis for local governments to formulate more effective and sustainable tax management strategies and improve the accuracy of taxpayer compliance. Thus, optimizing tax revenue can support the improvement of taxpayer services and compliance independently.